Computer knowledge required of librarians and information professionals by selected Philippine corporations - Rosales, Prudencio P., Jr.; Sison, Josephine C. (Quezon City Institute of Library Science, University of the Philippines Diliman, 1999)
Brought by the tremendous impact of computers on the corporate world and on information professions, employers nowadays prefer to hire jobseekers who are computer competent. This alarming trend has great effects to the LIPs because they are basically responsible for handling and processing information. In this connection, it is significant to know the computer knowledge requirement set by the employers of the corporate world.
This study was conducted to determine the computer knowledge required of LIPs by the country's first 100 leading corporations. This aimed to know the kinds and levels of computer literacy required by the said corporations, the new information technologies which they considered essential as entry level skills for the LIPs, the units/functions in which LIPs are needed and the position titles of the employed LIPs.
Findings showed that knowledge of word processing, spreadsheets, database design and management, computer graphics, programming languages and skill in accessing information using the Internet are the computer knowledge/skills required by the top 100 leading Philippine corporations. Database design and management and knowledge of word processing were found as the most required computer knowledge. Of all the corporate units/functions under study, LIPs are most needed in Library/Information Centers, in Database design and management as well as in Marketing/Promotions in all the business groups. Findings also showed that the selected corporations have various position titles for LIPs. Documentation officer, Information Resources Manager, Records Manager, Research Officer and Information Specialist are the most common position titles for the LIPs.
Based on the findings, it is recommended that LIPs must possess a basic knowledge in the processes and information services related to economics and business. It is further recommended that educational institutions teaching students to become LIPs must have a periodic evaluation of their curricula to make these more attuned to current trends in computer and communication technologies.
Vita.
Computer print out.
Thesis (Bachelor of Library and Information Science)
Keywords: Computer literacy -- Philippines -- Manila Metropolitan Area; Library employees -- Philippines -- Manila Metropolitan Area